2015
DOI: 10.3390/info6040811
|View full text |Cite
|
Sign up to set email alerts
|

Information and Phylogenetic Systematic Analysis

Abstract: Information in phylogenetic systematic analysis has been conceptualized, defined, quantified, and used differently by different authors. In this paper, we start with the Shannon Uncertainty Measure information measure I, applying it to cladograms containing only consistent character states. We formulate a general expression for I, utilizing a standard format for taxon-character matrices, and investigate the effect that adding data to an existing taxon-character matrix has on I. We show that I may increase when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
1
0
2
Order By: Relevance
“…The same measure was used by Carpenter (1993) to evaluate information contained within both cladistic and evolutionary (phyletic) classifications of fusilier fishes, in which more information for the latter was found. Another more recent mathematical contribution was by Craig & Stone (2015) who showed that as new apomorphic or synapomorphic characters were added to the data matrix, a cladogram gained in information content up to a certain limit. More studies of this nature are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The same measure was used by Carpenter (1993) to evaluate information contained within both cladistic and evolutionary (phyletic) classifications of fusilier fishes, in which more information for the latter was found. Another more recent mathematical contribution was by Craig & Stone (2015) who showed that as new apomorphic or synapomorphic characters were added to the data matrix, a cladogram gained in information content up to a certain limit. More studies of this nature are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Комплексний аналіз будови нервових волокон і васкуляризації лицевого нерва кроля в нормі та під час холодової нейронпатії дав можливість виявити назку загальних, морфометрично обґрунтованих, структурних і морфофункціональних рис, які мають теоретико-практичне значення. Співставляючи дані наших досліджень і відомості літератури, слід зауважити, що кількість нервових волокон на різних рівнях лицевого нерва пов'язана, перш за все, з ускладненням його плексусної будови, онто-та філогенетично зумовлена (Cohen et al, 2015;Craig and Stone, 2015). Ми встановили, що в лицевому нерві кроля число мієлінових нервових волокон коливається; це спостерігали також інші дослідники, які вивчали мієлоархітектоніку лицевого нерва та інших периферичних нервів тварин і людини (Azizzadeh et al, 2014;Fayad and Linthicum, 2014;Reina et al, 2015).…”
Section: обговоренняunclassified
“…Для розкриття патоморфологічних механізмів формування пошкоджень на тканинному та клітинному рівні значний інтерес являє вивчення адаптаційних реакцій організму за допомогою інформаційного аналізу (Craig and Stone, 2015). Тільки окремі автори присвятили свої дослідження вивченню інформаційних показників нервових волокон під час пошкодження периферичних нервів (Popel', 2017).…”
Section: обговоренняunclassified